Islamic work ethic and organizational citizenship behavior: The moderating role of religiosity among staff of JPPH Kelantan - Abdullah Thani, Ayu Kamareenna; Ismail, An Nur Nabila; Rosely, Nurhidayah; Nik Mohd Zainordin, Nik Mohamad Shamim; Muhamad, Mira Qerul Barriah; Ahmad, 6Nur Azreen Farihah (Journal of Islamic, Social, Economics and Development, 2025)
This study examines the influence of Islamic Work Ethic (IWE) on Organizational Citizenship Behavior (OCB), with Religiosity as a moderating variable among staff in the Valuation and Property Services Department (JPPH) Kelantan. A total of 217 questionnaires were distributed via Google Forms to employees, aligning with Krejcie and Morgan’s (1970) sample size determination for a population of 503. A valid response rate of 94.9% was achieved, with 206 completed responses analyzed using SPSS 28. The findings reveal a significant positive relationship between IWE and OCB, indicating that employees who adhere to Islamic work principles exhibit higher levels of discretionary workplace behaviors that benefit the organization. Moreover, Religiosity significantly moderates this relationship, strengthening the impact of IWE on OCB. Employees with higher religiosity are more likely to internalize and act upon Islamic ethical values, further enhancing their organizational commitment and pro-social behaviors. These results highlight the importance of integrating Islamic values into workplace ethics and management practices to foster a more engaged and cooperative workforce. Future research should explore additional moderating factors to deepen the understanding of work ethics and organizational behavior.